2017
DOI: 10.1371/journal.pntd.0005216
|View full text |Cite
|
Sign up to set email alerts
|

Yersinia enterocolitica, a Neglected Cause of Human Enteric Infections in Côte d’Ivoire

Abstract: BackgroundEnteropathogenic Yersinia circulate in the pig reservoir and are the third bacterial cause of human gastrointestinal infections in Europe. In West Africa, reports of human yersiniosis are rare. This study was conducted to determine whether pathogenic Yersinia are circulating in pig farms and are responsible for human infections in the Abidjan District.Methodology/Principal findingsFrom June 2012 to December 2013, pig feces were collected monthly in 41 swine farms of the Abidjan district. Of the 781 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 60 publications
3
21
0
Order By: Relevance
“…(Table 2). Surprisingly, this type has also newly been identified in pigs and humans in West Africa (36). Bioserotype 4/O:3 strains have also been found in pork, which appears to be an important infection source for human infections (3,74).…”
Section: Identification Of Yersinia Sppmentioning
confidence: 99%
“…(Table 2). Surprisingly, this type has also newly been identified in pigs and humans in West Africa (36). Bioserotype 4/O:3 strains have also been found in pork, which appears to be an important infection source for human infections (3,74).…”
Section: Identification Of Yersinia Sppmentioning
confidence: 99%
“…Yersiniosis is mainly caused by Yersinia enterocolitica, which is a facultative anaerobic Gramnegative bacterium that belongs to the Yersiniaceae family (Adeolu et al, 2016;Saraka et al, 2017). Yersiniosis is the third most common zoonotic disease in New Zealand and the most country of European Union (e.g., Germany and Finland) following campylobacteriosis and salmonellosis (Rosner et al, 2010;Strydom et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Gierczynski et al () showed that the MLVA type remained unchanged after 20 serial passages of a strain in vitro. In vivo, the same MLVA type was recovered from humans after repeated isolations from one or more patients with yersiniosis (Gierczynski et al, ; Sihvonen et al, ) as well as in pigs on farms when sampled at a 6‐month interval (Saraka et al, ). Thus, like PFGE profiles, MLVA types are likely to remain stable and survive unchanged for long periods.…”
Section: Discussionmentioning
confidence: 99%